The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1088/1674-1056/abf10a
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics study of coupled layer thickness and strain rate effect on tensile behaviors of Ti/Ni multilayered nanowires*

Abstract: Novel properties and applications of multilayered nanowires (MNWs) urge researchers to understand their mechanical behaviors comprehensively. Using the molecular dynamic simulation, tensile behaviors of Ti/Ni MNWs are investigated under a series of layer thickness values (1.31, 2.34, and 7.17 nm) and strain rates ( 1.0 × … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…[26] Effect of layer thickness and strain rate on mechanical properties of Ti/Ni multilayered nanowires is reported. [27] Bahramyan et al simulated the interaction between edge dislocation and void in pure Al and Al-Mg alloys. [28] Moreover, void growth in high entropy alloys has also been studied.…”
Section: Introductionmentioning
confidence: 99%
“…[26] Effect of layer thickness and strain rate on mechanical properties of Ti/Ni multilayered nanowires is reported. [27] Bahramyan et al simulated the interaction between edge dislocation and void in pure Al and Al-Mg alloys. [28] Moreover, void growth in high entropy alloys has also been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Periodic boundary conditions are maintained in x and y directions. [22][23][24] The substrates include the boundary, thermostat, and Newtonian layers (Fig. 1).…”
Section: Simulation Models and Methodsmentioning
confidence: 99%
“…Molecular dynamics (MD) simulation provides an alternative method to experiments, which plays an important role in understanding the deformation mechanism in metallic materials. [35][36][37][38] Actually, the mechanical properties of the crystalline/amorphous nanolaminates have been investigated in the past few years using MD simulation. [39][40][41][42] Tran and Fang [39] reported that the plastic deformation zones increase as the thickness of each layer decreases in crystalline/amorphous Cu/CuTa nanolaminates.…”
Section: Introductionmentioning
confidence: 99%